Cdc42 activation couples fluid shear stress to apical endocytosis in proximal tubule cells. Issue 19 (16th October 2017) - Bhattacharyya, Sohinee; Jean‐Alphonse, Frédéric G.; Raghavan, Venkatesan; McGarvey, Jennifer C.; Rbaibi, Youssef; Vilardaga, Jean‐Pierre; Carattino, Marcelo D.; Weisz, Ora A.
Abstract: Cells lining the kidney proximal tubule (PT) respond to acute changes in glomerular filtration rate and the accompanying fluid shear stress (FSS) to regulate reabsorption of ions, glucose, and other filtered molecules and maintain glomerulotubular balance. Recently, we discovered that exposure of PT cells to FSS also stimulates an increase in apical endocytic capacity (Raghavan et al. PNAS, 111:8506–8511, 2014 ). We found that FSS triggered an increase in intracellular Ca 2+ concentration ([Ca 2+ ]i ) that required release of extracellular ATP and the presence of primary cilia. In this study, we elucidate steps downstream of the increase in [Ca 2+ ]i that link FSS‐induced calcium increase to increased apical endocytic capacity. Using an intramolecular FRET probe, we show that activation of Cdc42 is a necessary step in the FSS‐stimulated apical endocytosis cascade. Cdc42 activation requires the primary cilia and the FSS‐mediated increase in [Ca 2+ ]i . Moreover, Cdc42 activity and FSS‐stimulated endocytosis are coordinately modulated by activators and inhibitors of calmodulin. Together, these data suggest a mechanism by which PT cell exposure to FSS is translated into enhanced endocytic uptake of filtered molecules. Abstract : Here we have dissected the steps downstream of calcium release that contribute to fluid shear stress‐stimulated endocytosis. Using FRET imaging, calcium measurements, and quantitation of endocytic uptake, we demonstrate that activation of Cdc42 is required for FSS‐stimulated endocytosis. Moreover, we show that Cdc42 activation is mediated by calmodulin downstream of FSS‐triggered changes in intracellular calcium concentrations.